Memory and Built Space: Reaction of Contemporary Sri Lankan Visual Artists - Kirubalini, S. (Proceedings of Peradeniya University International Research Sessions 2021, Sri Lanka, Vol. 23, 11th & 12th November 2021, 2021)
Contemporary Sri Lankan visual artists represent social and political issues around them through individual or collective experiences and memory. Meanwhile, the art forms are also wide-ranging based on the theoretical and conceptual approaches of each artist. Themes of many contemporary artists are related to narrating ―Memory of war and violence‖ in different ways. In our country, many studies have been done on the relationship between memory and the field of arts. A Virtual Museum has also been initiated to bring art initiatives and multimedia resource material together in one place. Memory studies is one of the interesting topics in humanities and social science studies. Without memory, humans cannot exist; we relate our memories not only with objects and people, but also with space and architecture, space and architecture can have an impact on individual memories as much as on collective memories. In this background, this research is focused on the relationship between memory and visual artwork by six selected contemporary visual artists from Tamil speaking regions of Sri Lanka. The aim of the study is to analyse the relationship between the representations of each artist and memories behind the built spaces such as memorials, public buildings and houses or which were considered as house. The research extensively focused on the ways in which the artists embody memories through book art, installation, drawing, collage and mixed media, and the social, political, personal background influenced on their art works. The author comes from an Art History background and has attempted to answer these research questions using pictorial and analytical works from multidisciplinary approaches and applying memory theory. This Research paper reveals how the narrative of a built space has been transformed by artists and how the artists (re)visit, (re)shape, (re)store and (re)build memory.
Keywords: Memory; Personal; Collective; Context; Built forms